Parametric analysis of a circulating fluidized bed biomass gasifier for hydrogen production - Chutichai, Bhawasut; Patcharavorachot, Yaneeporn; Assabumrungrat, Suttichai; Arpornwichanop, Amornchai (My University, 2015)
Biomass is considered a potential energy source which can be efficiently converted to useful gaseous products via a gasification process. Circulating fluidized bed (CFB) gasifiers have attracted significant attention due to their high reaction rates and thermal efficiency. This study aims to investigate the CFB biomass gasification process to generate H2-rich synthesis gas. A process simulator is used to analyze the gasifier performance by assuming that the gasification is fast and reach equilibrium. Parametric analysis of the CFB gasifier shows that steam gasification generates the synthesis gas attained the highest H2 content (50-65vol.%) and the highest product gas quality (higher heating value, HHV=10-13MJ/Nm3) at operating temperatures approximately 650-700°C. High-temperature steam cannot provide enough energy for the gasifier, reducing the gross cold gas efficiency of this process to only 16%. The biomass air-steam gasification process is investigated while avoiding high energy consumption, but less H2 is produced under these conditions.
Keywords: Biomass; Circulating fluidized bed gasifier; H2-rich synthesis gas; Performance analysis